Malawi Strategy Support Program (MaSSP) - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
he IFPRI Malawi Strategy Support Program (MaSSP) works closely with the Malawian government, particularly the Ministry of Agriculture, Irrigation and Water Development (MoAIWD), Department of Agricultural Planning Services (DAPS), to support these goals and facilitate and promote evidenced-based dialogue and decisionmaking, by providing both technical and analytical support. Particular emphasis is placed on supporting Malawi’s Agricultural Sector-Wide Approach (ASWAp) – an agenda designed to accelerate agricultural growth through prioritization and harmonization of public resource allocation.